(untitled) (Research, Society and Development, 2021)
Currently several industries such as mining, galvanoplastics, tanneries, electronics manufacturers and others, throw effluents containing heavy metals into the water bodies contaminating them. Another factor that contributes to water contamination are pesticides and fertilizers thrown into the soil, which end up being dragged by rain to rivers and lakes. Drinking water, a basic and indispensable resource for life, has been minimized due to the discharge of industrial effluents containing heavy metals such as chromium, lead and cadmium. The search for new treatment options for these tailings is becoming more and more frequent and the use of moringa oleifera, a Indian plant that can be used as a biosorbent, stands out for its coagulant and flocculant properties and for being an easy-to-handle organic material. The objective of this work is to evaluate the adsorption potential of the moringa oleifera seed, for this the seeds were evaluated after hot solvent extraction by Soxhlet with n-hexane and oven dried for 24 hours at 60 ° C, proposed methodology by Costa et al. (2013). K2Cr2O7 solutions of 0.01 mol.L-1 concentration were prepared and the solutions were kept under magnetic stirring for 24 hours with 0.5 g of adsorbent material, filtered and analyzed by UV / VIS spectrophotometry, methodology adapted from Tavares et al. al. (2015). The average lipid content found in the seed dust, crushed seed and peel was 30.2%, 26.7% and 4.7% respectively, while the average moisture content was 7.1%, 6.0% and 6.8%. Based on the adsorption result, the seed dust showed potential for removal of 43% of chromium (VI), while the crushed seed had a removal potential of 7.4% and the peel 12.6%.